TiO2 and N-Doped TiO2 Induced Photocatalytic Inactivation of Staphylococcus aureus under 405 nm LED Blue Light Irradiation - Hongfei Chen; Zhong Xie; Xiujuan Jin; Chao Luo; Chao You; Ying Tang; Di Chen; Zhengjia Li; Xiaohong Fan (International Journal of Photoenergy)
Irradiation source has been a serious impediment to induce photocatalytic bacterial inactivation which was taken as an advanced indoor air purification technique. Here we reported the synergistic effects of 405 nm LED light and TiO2 photocatalyst in inactivation process of Staphylococcus aureus (S. aureus). In this work, TiO2 and N-doped TiO2 particles were, respectively, suspended into the nutrient broth suspension with S. aureus. Then, the mixed system was exposed to a 405 nm LED light source with energy density of about 0.2 W/cm2 for 3 hours. Irradiated suspension was then scanned by UV-vis spectrophotometer for bacteria survive/death rate statistics. Subsequently, the inactivation efficiency was calculated based on the difference of the absorption optical density between experimental and controlled suspensions. Results showed that both TiO2 and N-doped TiO2 particles exhibit potential bacterial inactivation effects under similar experimental conditions. Specifically, N-doped TiO2 with the concentration of 5 g/L displayed enhanced inactivation efficiency against S. aureus under 405 nm LED light irradiation. Thus, it is a promising indoor air purification technique by using N-doped TiO2 particles under the LED light irradiation.